Medical termination of pregnancy (Amendment) Act 2021: From the lenses of LGBTQIA+ community in India - Atul Shendge; Abhishek Royal; Alpana Dange; Vaibhav Kumar (Journal of Family Medicine and Primary Care)
The article presents the LGBTQIA + inclusivity analysis of the Medical Termination of Pregnancy (Amendment) Act 2021, which aims to provide safe abortion services across India. The analysis reports the use of cisgender-heteronormative language, instead of gender-neutral terms and pronouns in the legislation. Sexual assault/rape as an eligibility criterion for permitting abortion under this act does not apply to non-binary, trans- and queer individuals due to non-inclusivity in Rape Laws (Indian Penal Code 375 and 376). The analysis highlights the necessity for critical amendments to expand its scope to ensure LGBTQIA+ inclusive abortion services.